2021
DOI: 10.1021/acs.iecr.0c05963
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the In Situ Creation of an Epoxy Based Thermosetting Minor Phase on the Physical Properties of a PP Based Blend

Abstract: As an alternative to inorganic fillers based composites which present high density, an epoxy based thermosetting (TS) phase was in situ created in a polypropylene (PP) matrix and compatibilized by a polypropylene grafted maleic anhydride (PP-g-MA).The aim of this study is to scrutinize the chemistry and establish a relation between the morphology, the mechanical properties and the crystalline structure of this thermosetting/thermoplastic system. Depending of the components concentration, dispersed phase of aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Morphological analysis revealed that the dispersion of PES nodules was 10 times finer in the case of in situ polymerization. Similarly, Barroso Gago et al [17] prepared PP/PP--g--MA/thermoset blends with the in situ synthesis of an epoxy based thermosetting phase by reactive extrusion. Thanks to the in situ synthesis, they observed a very fine dispersion of the thermoset phase in polypropylene with nodules of 0.5µm in diameter.…”
Section: Morphology Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphological analysis revealed that the dispersion of PES nodules was 10 times finer in the case of in situ polymerization. Similarly, Barroso Gago et al [17] prepared PP/PP--g--MA/thermoset blends with the in situ synthesis of an epoxy based thermosetting phase by reactive extrusion. Thanks to the in situ synthesis, they observed a very fine dispersion of the thermoset phase in polypropylene with nodules of 0.5µm in diameter.…”
Section: Morphology Developmentmentioning
confidence: 99%
“…The PA6 particle size was reduced from >2µm to <0.5µm in the presence of the compatibilizing agent PP--g--MA. More recently in our group, Barroso Gago et al [17] developed PP/PP--g--MA/thermoset blends with the in situ synthesis of the epoxy based thermoset phase in a twin--screw extruder at 200°C. The thermoset phase (TS) was well dispersed in the PP matrix, with TS domains around 0.5 µm in diameter.…”
Section: Introductionmentioning
confidence: 99%